ETIQUETTE OF GUEST AND HOST - Axmedov Azimjon; Xakimova Gulxumor (Journal of new century innovations, 2023)
Annotation: This scientific article delves into the etiquette of guest and host, examining the cultural norms and social dynamics that shape this important interpersonal relationship. Drawing from the fields of sociology, anthropology, and cultural studies, the article explores the roles, responsibilities, and expectations of both guests and hosts across different cultural contexts. By analyzing the underlying principles and practices of guest-host interactions, this article aims to enhance our understanding of the etiquette involved and its significance for social harmony, hospitality, and intercultural communication.